Islamic Value-Based Leadership and Modern Organizational Management as a Foundation HMI cadres - Fitra Hadi Khaz; Refdi Refdi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This Community Service Program (PKM) aims to enhance the leadership capacity and organizational management skills of cadres of the Islamic Student Association (HMI) Dumai Branch through the strengthening of Islamic values and the application of modern organizational management principles. The program was implemented as part of the Intermediate Training (Latihan Kader II/LK 2), which serves as a strategic forum for developing future organizational leaders. The activities were conducted using a combination of lectures, interactive discussions, case-based learning, and leadership simulations designed to encourage critical thinking and active participation. A participatory approach was employed to ensure that participants were directly involved in the learning process and could relate the material to real organizational challenges. The results of the program indicate a significant improvement in participants’ understanding of transformational leadership, collective–collegial leadership, and effective organizational planning and management skills. In addition, the program increased participants’ awareness of the importance of integrating Islamic values as an ethical and moral foundation in student organizational leadership practices. Overall, this PKM contributes to the development of qualified HMI cadres who possess integrity, adaptability, strong leadership competence, and a sustained commitment to community service and organizational development.